Cytological Diagnosis of Pleural Effusions Based on the International System for Reporting Serous Fluid Cytopathology and Its Histopathological Correlation - Sayaniya, Mayur; Joshi, Hetal (Annals of Pathology and Laboratory Medicine, 2025)
Background: This study classifies pleural fluid cytology using the International System for Reporting Serous Fluid Cytopathology (TIS, 2021) and evaluates the Risk of Malignancy (ROM) through histopathological correlation. Conducted over two years at a tertiary care hospital, it aims to assess the diagnostic and prognostic value of TIS in managing serous effusions. Materials and Methods: Pleural fluid samples were categorized using the International System for Reporting Serous Fluid Cytopathology, and histopathological slides were reviewed to assess the ROM. Statistical analysis was performed using descriptive statistics, and diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy were calculated to evaluate the effectiveness of the TIS classification in predicting malignancy. Results: Among 260 cases, 4 (1.53%) were Non-Diagnostic (ND), 214 (82.31%) Negative for Malignancy (NFM), 9 (3.46%) Atypia of Undetermined Significance (AUS), 9 (3.46%) Suspicious for Malignancy (SFM), and 24 (9.23%) Malignancy (MAL). ROM was 33.33% in ND, 19.86% in NFM, 50% in AUS, 66.67% in SFM, and 50% in MAL. Sensitivity, specificity, and diagnostic accuracy varied across categories. Conclusion: TIS is a reliable system for reporting pleural effusions. ROM is highest in the AUS, SFM, and MAL categories. Consistency in diagnostic criteria and further refinement in ND and NFM categories are necessary for improved clinical outcomes.